Cefepime versus extended spectrum β-lactamase-producing Enterobacteriaceae - Nogueira,Keite da Silva (2011)
The objective of this study was to evaluate the susceptibility to cefepime of a large group of ESBL- producing enterobacteria recently isolated in a Brazilian teaching hospital . The study included 280 strains of ESBL-producing enterobacteria, isolated between 2005 and 2008. The presence of the genes blaCTX-M, blaTEM and blaSHV was determined by PCR and confirmed by nucleotide sequencing. Susceptibility testing for cefepime was performed by disc-diffusion, agar dilution method and E-test®. Among the isolates, 34 (12.1%) presented a cefepime inhibition zone > 21 and MIC < 8 mg/L by agar dilution and E-strip methods. The use of cefepime for the treatment of infections caused by ESBL-producing bacteria has been controversial. Some studies of PD/PK show the probability of achieving the required PD parameters for cefepime, when the MICs were < 8 mg/L, whereas others have reported therapeutic failure with the same MIC. Additional data is essential to come to terms about the report and treatment with cefepime in ESBL-producing organisms especially when these microorganisms are isolated from sterile sites and from critically ill patients.